STUDI KOMPARATIF MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) DAN STAD (STUDENT TEAM ACHIEVEMENT DIVISION) TERHADAP HASIL BELAJAR PADA MATAKULIAH AKUNTANSI DI UNIVERSITAS ISLAM NEGERI (UIN) MALANG - Kusumadyahdewi, Kusumadyahdewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Purpose of this research is to understand the differences of learning outcomes using Cooperative learning model type TAl (Team Assisted Individualization) and STAD (Student Team Achievement Division) on the subject Accounting, Social Sciences Education Department of Tarbiyah and Teaching Sciences of Maulana Malik lbrahim State Islamic University of Malang. This research using Experimental research design Quasi Experiment, and the model using Pre-Test and Post-Test Control Group Design. Population of this research is all students of first semester Year 2013/2014, and the sample are class A as the experiment group who using TAI model and class B as the control group who study using STAD model. There are two instruments in this research, such as treatment instrument and measurement instrument. Researcher used hypothesis test to know the differences of learning outcomes, t-test in which previously conducted the prerequisite test analysis which consist of normality test, homogeneity test, and the equality test of average initial ability of student. Result of this research shows the difference of average mark in cognitive aspects in these classes is not significant but the average mark TAI class higher than STAD class, but there is a significant difference in psychomotor aspects in these classes. It can be showing the average mark of TAI also higher than STAD.Keywords: Learning Outcomes, Cooperative Learning Model type TAI, STAD